Medical Profession: A Career Choice for females of Fatima Jinnah Medical College, Lahore - ,SADAF RASHID, ANJUM SHAFI, MISS SAIMA LIAQUAT, RAKSHANDA FARID (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To find out the factors associated for choosing medicine as a profession. Method: The study was done at Fatima Jinnah Medical College. The study design was a cross sectional survey.Onehundred female medical students answered a close ended questionnaire. The results were analyzed by using Pearson’s coefficient correlation. Results: 76% responded that they chose the medical profession on their own determination, 83% responded that it was their parent’s desire to choose this profession, 88% of the students thought that it is a respectable profession for females. Eighty one percent of the students thought by choosing this field they will be able to explore new dimensions in health, where as 69% thought that by becoming a doctor they can improve the health conditions of Pakistan. Seventy percent had a childhood desire to become a doctor and 72% thought after graduation they will become independent, 95% wanted to serve humanity. However 78% had other alternatives but they preferred this profession. One third of the students had their siblings as doctors. There was a significant positive correlation between choosing the medical profession and exploring new dimensions in health, serving the humanity, becoming independent, and improving the health status of the community (p≤0.01). Conclusions: Most of the students chose the field on their own and wanted to serve the humanity and also they wanted to explore new dimensions in health and were happy that they selected the profession.